Pemberdayaan ekonomi masyarakat pelaku usaha UMKM di Kelurahan Limbungan Kecamatan Rumbai Pesisir Kota Pekanbaru - Sri Endang Kornita; Syafril Basri; Restu Restu; Ufira Isbah; Selly Prima Desweni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The community service activities carried out are Community Economic Empowerment of MSME Entrepreneurs in Limbungan Village, Rumbai Pesisir District, Pekanbaru City. This activity integrated with the implementation of the Student Community Service Program of 2020. The role of the community service team is business management training (financial management, taxation), strategy of business development, and accompaniment for the 19 MSME entrepreneurs in this area that participated. The aims of this community service activity are to improve understanding and implementation of MSME management in a professional, efficient, and effective way, with the result that can manifest independence and well-being of the community to optimize the existing potential. It is also expected that this training will provide an added value for the community development of MSME entrepreneurs’s business. This training can change community behavior into more creative and improve community income in this area. The training methods are a combination between lectures and accompaniment, where participants will obtain material manual books about finance and taxation of MSME. It can be seen that the participants have more understanding about bookkeeping and finance of MSME, taxation, and online marketing after participating in the integrated community service and student community service program of LPPM UNRI.